Patients with low IGF-I after curative surgery for Cushing's syndrome have an adverse long-term outcome of hypercortisolism-induced myopathy. Issue 6 (4th May 2021) - Vogel, Frederick; Braun, Leah; Rubinstein, German; Zopp, Stephanie; Benedix, Sarina; Schneider, Holger; Ritzel, Katrin; Schilbach, Katharina; Schmidmaier, Ralf; Beuschlein, Felix; Bidlingmaier, Martin; Reincke, Martin
Abstract : Background: Glucocorticoid excess leads to muscle atrophy and weakness in patients with endogenous Cushing's syndrome. Insulin-like growth factor I (IGF-I) is known to have protective effects on muscle loss. We hypothesized that individual serum IGF-I concentrations might be predictive for long-term myopathy outcome in Cushing's syndrome. Patients and methods: In a prospective longitudinal study of 31 patients with florid Cushing's syndrome, we analyzed IGF-I and IGF binding protein 3 (IGFBP 3) concentrations at the time of diagnosis and following surgical remission over a period of up to 3 years. We assessed muscle strength by grip strength measurements using a hand grip dynamometer and muscle mass by bio-impedance measurements. Findings: Individual serum IGF-I concentrations in the postoperative phase were strongly predictive of long-term grip strength outcome (rs  = 0.696, P ≤ 0.001). Also, lower IGF-I concentrations were associated with a lower muscle mass after 3 years (rs  = 0.404, P   = 0.033). While patients with high IGF-I s.d. scores (SDS; >1.4) showed an improvement in grip strength within the follow-up period ( P   = 0.009), patients with lower IGF-I SDS (≤−0.4) had a worse outcome with persisting muscle dysfunction. In contrast, preoperative IGF-I concentrations during the florid phase of Cushing's syndrome did not predict long-term muscle function outcome (rs  = 0.285, P   = 0.127). Conclusion: Lower individual IGF-I concentrations 6 months after curative surgery for Cushing's syndrome are associated with adverse long-term myopathy outcome and IGF-I might be essential for muscle regeneration in the early phase after correction of hypercortisolism.